2014
DOI: 10.1152/ajpgi.00183.2013
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned medium from Bifidobacteria infantis protects against Cronobacter sakazakii-induced intestinal inflammation in newborn mice

Abstract: Weng M, Ganguli K, Zhu W, Shi HN, Walker WA. Conditioned medium from Bifidobacteria infantis protects against Cronobacter sakazakii-induced intestinal inflammation in newborn mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 42 publications
(48 reference statements)
2
36
0
Order By: Relevance
“…These experiments suggest that B. infantis produce exogenous substances that promote maturation of the immature innate immune response (68). This supernatant from B. infantis attenuates Cronobacter sakazakii- induced enteritis in a newborn mouse model ( C. sakazakii is a contaminant of powdered infant formulas associated with both sepsis and NEC in premature infants) (69). In a rat model of NEC, administration of B. infantis decreased expression of IL6, IL8, TNFα, IL23, and iNOS, decreased the expression of antimicrobial peptides, altered expression of intestinal mucus-related proteins, and decreased the incidence of NEC (17).…”
Section: Mechanisms Of Observed Protective Effectsmentioning
confidence: 99%
“…These experiments suggest that B. infantis produce exogenous substances that promote maturation of the immature innate immune response (68). This supernatant from B. infantis attenuates Cronobacter sakazakii- induced enteritis in a newborn mouse model ( C. sakazakii is a contaminant of powdered infant formulas associated with both sepsis and NEC in premature infants) (69). In a rat model of NEC, administration of B. infantis decreased expression of IL6, IL8, TNFα, IL23, and iNOS, decreased the expression of antimicrobial peptides, altered expression of intestinal mucus-related proteins, and decreased the incidence of NEC (17).…”
Section: Mechanisms Of Observed Protective Effectsmentioning
confidence: 99%
“…42 Culture medium from B. infantis decreases the severity of infection with C. sakazaki in the mouse with attenuation of three mechanisms of pathogenesis: induction of IL1β and TNFα, decrease in mucin production, and increase in apoptosis. 43 …”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…In studies from this laboratory (73), we have identified a secreted product from the same B. infantis which on partial characterization is likely a glycan of less than 30 kD size. This factor has an anti-inflammatory effect in a fetal small intestinal cell line (H4) and functions by causing a maturation of the innate inflammatory immune response to an inflammatory stimulus with a reduction in the expression of TLR-4, its signaling molecules and its transcription factor NFκB genes and an increase in negative regulators of this response (TOLLIP, SIGIIR, and A-20) as seen in mature enterocytes (73,74). Finally, a recent study of the molecular response of intestinal bacteria to breast vs. infant formula feeding has shown that the products of breastfed intestinal bacteria have a greater effect on protective genes in enterocytes than products of formula-fed infants (75).…”
Section: Breastfeeding and Intestinal Colonizationmentioning
confidence: 99%